A Rare Combination of Ovarian and Uterine Leiomyomas with Goblet Cell Carcinoid of the Appendix - Abdulrahman F. Al-Shaikh; Abdulla Darwish; Veena Nagaraj; Abeer Alsada (Case Reports in Surgery)
We present a case of the rare combination of unilateral ovarian leiomyoma, uterine leiomyoma, and goblet cell carcinoid tumor of the appendix in a premenopausal woman who presented with right iliac pain. Immunohistochemistry study for desmin (muscle marker) and chromogranin and synaptophysin (neuroendocrine markers) confirmed immunophenotyping origin. Interestingly, both tumors showed positive reaction for estrogen receptor. To our knowledge, such a combination has not been reported previously in the literature. In this paper, the pathogenesis and differential diagnosis of both types of tumors are discussed.